Post-transcriptional diversity in riboproteins and RNAs in aging and cancer. (November 2021) - Cruz, Jurandir; Lemos, Bernardo
Abstract: Post-transcriptional (PtscM) and post-translational (PtrnM) modifications of nucleotides and amino acids are covalent modifications able to change physio-chemical properties of RNAs and proteins. In the ribosome, the adequate assembly of rRNAs and ribosomal protein subunits in the nucleolus ensures suitable translational activity, with protein synthesis tuned according to intracellular demands of energy production, replication, proliferation, and growth. Disruption in the regulatory control of PtscM and PtrnM can impair ribosome biogenesis and ribosome function. Ribosomal impairment may, in turn, impact the synthesis of proteins engaged in functions as varied as telomere maintenance, apoptosis, and DNA repair, as well as intersect with mitochondria and telomerase activity. These cellular processes often malfunction in carcinogenesis and senescence. Here we discuss regulatory mechanisms of PtscMs and PtrnMs on ribosomal function. We also address chemical modification in rRNAs and their impacts on cellular metabolism, replication control, and senescence. Further, we highlight similarities and differences of PtscMs and PtrnMs in ribosomal intermediates during aging and carcinogenesis. Understanding these regulatory mechanisms may uncover critical steps for the development of more efficient oncologic and anti-aging therapies.